2022
DOI: 10.53854/liim-3001-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of COVID-19 characteristics in Egyptian patients according to their Toll-Like Receptor-4 (Asp299Gly) polymorphism

Abstract: Background: Toll-like receptor (TLR)-4 plays a vital role in recognizing viral particles, activating the innate immune system, and producing pro-inflammatory cytokines. Objectives: This cross-sectional study aimed to compare COVID-19 severity, progression, and fate according to TLR-4 (Asp299Gly) polymorphism in Egyptian patients. Methods: A total of 145 COVID-19 patients were included in this study. TLR-4 (Asp299Gly) genotyping was done using the PCR restriction fragment length polymorphism (PCR-RFLP) approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…In contrast to our observations, Taha et al found that the Gallele of rs4986790 was associated with a significantly higher risk of severe COVID-19 (N = 300, OR = 3.14, 95% CI = 2.02 -4.88, p < 0.001) in a cohort of Egyptian patients (18). The authors also observed a significant increase in IL-6 levels in carriers of the rs4986790 G-allele, which we could not confirm in our study (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our observations, Taha et al found that the Gallele of rs4986790 was associated with a significantly higher risk of severe COVID-19 (N = 300, OR = 3.14, 95% CI = 2.02 -4.88, p < 0.001) in a cohort of Egyptian patients (18). The authors also observed a significant increase in IL-6 levels in carriers of the rs4986790 G-allele, which we could not confirm in our study (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…The genotype distribution and allele frequency of the studies on susceptibility and severity are summarized in Table 2 and Table 3 , respectively. The studies for susceptibility analysis included: ACE1 I/D rs4646994/rs1799752 ( Annunziata et al, 2021 Aug 20 , Gong et al, 2021 , Aladag et al, 2021 Sep , Papadopoulou et al, 2022 Mar , Akbari et al, 2022 Feb , Calabrese et al, 2021 Jan , Saad et al, 2021 Dec , Möhlendick et al, 2021 Oct 1 , Gómez et al, 2020 Dec , Hubacek et al, 2021 Aug , Kouhpayeh et al, 2021 Nov 17 , Mahmood et al, 2022 Feb , Mir et al, 2021 Oct 27 ); ACE2 rs2285666 ( Möhlendick et al, 2021 Oct 1 , Alimoradi et al, 2022 Mar 19 , Gómez et al, 2020 Dec , Mahmood et al, 2022 Feb ); APOE rs429358 ( Kuo et al, 2020 May 26 , Al-Jaf et al, 2021 Nov , Hilser et al, 2021 Jan ); CCR5 rs333 ( Cuesta-Llavona et al, 2021 Sep , Bernas et al, 2021 Apr , Gómez et al, 2020 ); IFITM3 rs12252 ( Abbas et al, 2021 Jun 12 , Schönfelder et al, 2021 Jun , Gómez et al, 2021 Jan ); TMPRSS2 rs12329760 ( Taha et al, 2022 Mar 1 , Andolfo et al, 2021 , Schönfelder et al, 2021 Apr , Wulandari et al, 2021 ), and TNFA rs1800629 ( Rokni et al, 2022 Apr , Saleh et al, 2020 Nov , Heidari Nia et al, 2022 ). Severity-wise analysis was performed for ACE1 I/D rs4646994/rs1799752 ( Karakaş Çelik et al, 2021 Oct , Gong et al, 2021 , Gunal et al, 2021 Jun , Martínez-Gómez et al, 2022 Feb , Baştuğ et al, 2021 Dec 8 , Akbari et al, 2022 Feb , Saad et al, 2021 Dec , Möhlendick et al, 2021 Oct 1 , Cafiero et al, 2021 May , Gómez et al, 2020 Dec , Hubacek et...…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the S-protein induces innate immune activation via Toll-like receptors TLR2 and TLR4 ( 24 , 25 , 27 , 64 ) and in silico modeling suggests that it may direct interact with TLRs ( 65 ). TLR expression levels correlate with markers of organ injury in COVID-19 ( 66 ) while genetic polymorphisms in TLR2 and TLR4 are associated with COVID-19 outcomes ( 67 , 68 ). Thus, the TLR axis may contribute significantly to the inflammation observed with SARS-CoV2 infection.…”
Section: Discussionmentioning
confidence: 99%